A systematic review of physical and psychological health and wellbeing of older women in Sub-Saharan Africa. (7th March 2019) - Mangipudi, Sowmya; Cosco, Theodore; Harper, Sarah
Abstract: Background: Sub-Saharan Africa (SSA) has the fastest growing proportion of older adults in the world, the majority of whom are women. Global health agendas, however, continue to deprioritise older women's health issues, including the incidence of and mortality from non-communicable disease (NCDs). This is the first systematic review to address the health, wellbeing and healthcare utilization of older SSA women. Methods: Studies with primary analysis of health, wellbeing and/or healthcare utilization outcomes for women over the age of 50 from SSA countries were included. Databases searched include EMBASE, Scopus and Psycinfo. Findings: About 26 studies from six SSA countries met inclusion criteria. Studies regarding NCDs predominated ( n = 12), followed by healthcare utilization ( n = 4), disability ( n = 4), wellbeing ( n = 2), depression ( n = 2) and HIV ( n = 2). Every study indicated significantly lower self-rated health and wellbeing, higher rates of depression, hypertension, obesity, disability or weakness for women compared with men. The studies also indicated that older women use healthcare more often, and choose public over private facilities more often. Interpretation: The studies in the review had large, diverse samples. This review demonstrates the need for more gender-specific studies to better understand the unique challenges older women face in managing NCDs in particular.